Saving more lives on time: Strategic policy implementation and financial inclusion for safe abortion in Indonesia during COVID-19 and beyond - Saraswati, Putri Widi (Frontiers in Global Women's Health, 2022)
Abortion is common in Indonesia. 79% are unsafe. Unsafe abortion is one of the top 5 causes of maternal deaths globally. Meanwhile, Indonesia’s Maternal Mortality Rate (MMR) is still high. In the COVID-19 pandemic, the number of unsafe abortions is expected to increase. This will add to the number of maternal deaths on top of direct deaths caused by COVID-19. Indonesia already has legal grounds for safe abortion, but there are gaps in implementation and in the financing, especially in the era of the national health insurance scheme (Jaminan Kesehatan Nasional/JKN). This brief aims to guide how to equitably implement and inclusively finance safe abortion in Indonesia – in and beyond the COVID-19 pandemic – to gain maximum socioeconomic benefit and leave no one behind.